DISCUSSION ON OPTIMAL TREATMENT STRATEGIES FOR OVARIAN ENDOMETRIOSIS - Nadjmitdinova D.A., Asrankulova D.B. (Central Asian Journal of Medicine, 2025)
Ovarian endometriosis is a prevalent gynecological condition associated with chronic pelvic pain, infertility, and decreased ovarian reserve. Despite its frequency, the optimal surgical approach remains controversial due to variability in diagnostic criteria and the potential risks associated with operative interventions. According to global estimates, endometriosis affects approximately 10–15% of women of reproductive age, with ovarian endometriomas observed in up to 44% of these cases. The burden of disease is particularly significant due to diagnostic delays, often averaging 7–10 years from symptom onset to confirmed diagnosis.